(untitled) - Myrdal, Gunnar (New York, 1968)
Professor Myrdal began with a hopeful view of the possibilities for rational planning and ordered growth in the underdeveloped countries; in the course of his work he has come to a somber realization of the difficulties they must surmount and the need for a reappraisal of the theories basic to their planning efforts. He is understandably reluctant to admit how largely thinking about the underdeveloped countries has been shaped and influenced by his own studies; yet unless one realizes this, the achievement of the present volume is not fully weighted. For Professor Myrdal had not only to move against accepted premises and assumptions; what was more difficult, he had to move against those premises which he had himself done so much to establish and to make seem self-evident. Burke says somewhere that there is no vested interest so powerful as the vested interest in an idea. When the idea is of one's own making, the efforts required to transcend it may be nothing less than heroic.
Keywords: Economics